Conformationally Selective Synthesis of Mononitrocalix[4]arene in Cone or Partial Cone. Issue 5 (10th May 2017) - Royappa, Ana Rita N. S.; Ayer, Maxime; Fracassi, Alessandro; Ebert, Marc‐Olivier; Aroua, Safwan; Yamakoshi, Yoko
Abstract : Nitro‐substituted calixarenes in a cone and a partial cone conformation were prepared selectively using distinct synthetic routes. The selective nitration of tris‐ or penta‐substituted phenols of calix[4]arene or calix[6]arene provided mononitrocalix[ n ]arenes ( n  =   4, 6). Subsequent addition of ethylene glycol (EG) moieties to mononitrocalix[4]arene provided tetraEGylcalix[4]arene in locked partial cone conformation. By an alternative route – initial addition of EG moieties to the non‐derivatized calix[4]arene followed by the uncontrolled nitration – provided mononitro‐ and dinitro‐tetraEGylcalix[4]arenes locked in the cone conformation. These nitrocalix[4]arenes with locked cone or partial cone conformation are useful building blocks for further assembly of supramolecular systems, especially in the area of material sciences. Abstract :